“The key to all political organization”: Moderating Power in the constitutional history of Brazilian Empire - Lynch, Christian Edward Ciryl (História do Direito, 2025)
This article examines the trajectory of the Moderating Power in the constitutional history of the Brazilian Empire, from its origins in European thought to its establishment in the 1824 Constitution. It highlights the divergent interpretations during the Second Reign, with liberals such as Zacarias de Góis and Rui Barbosa advocating its subordination to Parliament, while conservatives like the Viscount of Uruguai and Pimenta Bueno defended its autonomy as a stabilizing element of the regime. Brás Florentino radicalized this view, attributing an absolute character to it, while Tobias Barreto, from a scientific perspective, criticized the artificiality of the debate and the inapplicability of parliamentarism in Brazil. The study demonstrates how these disputes shaped Brazilian constitutionalism and influenced republican politics.